Analisa Kategori Barang dengan Penjualan Terbanyak dalam Jangka Waktu 3 Bulan Menggunakan Data Warehouse - Eka Pratama, I Putu Agus; Bernard, Rey (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
UD. Makmur Sejahtera as one of the largest distributors of daily necessities in Manokwari Papua has sales transaction data for each category of goods and types of goods. These data are still physically stored in the form of notes and have not been digitized so that they can be utilized optimally to help UD. Makmur Sejahtera increases sales. This research has the basic idea of using digital sales transaction data to find out which categories of goods have the most sales in a period of three months (July 2020 to September 2020) through the Extraction, Transformation, Loading (ETL) process based on Pentaho Data Integration, to then be stored in multi-dimensional data forms, categorized, and visualized using Tableau. The test results show that rice commodity is the category of goods with the most sales in a period of three months and the implementation of the Data Warehouse is very helpful for UD. Makmur Sejahtera in achieving its business goals.